MODEL PEMBELAJARAN QUANTUM TEACHING DENGAN MEDIA FLASH DALAM PEMBELAJARAN FISIKA DI SMA - Hilmi Fathiyatul Baroroh; Trapsilo Prihandono; Subiki Subiki (JURNAL PEMBELAJARAN FISIKA, 2017)
This research focuses on the application of Quantum Teaching learningmodel with Flash media. The purpose of this research were: (1) to examine thedifference of student achievement between student in Quantum Teaching learningmodel with Flash media class and students conventional learning model class; (2) todescribe of students learning activity using Quantum Teaching learning model withFlash media. The type of this research is an experimental research. This researchheld in SMAN 5 Jember using design post-test only control. The technique of datacollection in this research were observation, documentation, and test. Data analysistechniques was independent sample t-test from SPPS 16. Based on data analysis anddiscussion, the conclusion of this research were: (1) there was a significantdifferences of student achievement between student in Quantum Teaching learningmodel with Flash media class and students conventional learning model class;(2)students learning activity using Quantum Teaching learning model with Flash mediawas classified in very active criteria.Keywords: Students learning activity, Students achievement, Flash media,Quantum Teaching Learning model.